183. Optimization of an Outpatient Antimicrobial Stewardship Process for Patients Discharged from the Emergency Department at an Academic Medical Center. (31st December 2020) - Kafisheh, Hannah; Hinton, Matthew; Binkley, Amanda; Cimino, Christo; Edwards, Christopher
Abstract: Background: Suboptimal antimicrobial therapy has resulted in the emergence of multi-drug resistant organisms. The objective of this study was to optimize the time to antimicrobial therapy modification for patients discharged from the emergency department (ED) of an academic medical center through implementation of a pharmacist-driven outpatient antimicrobial stewardship initiative (ASI). Methods: This was a pre-post, quasi-experimental study that evaluated the impact of a pharmacist-driven outpatient antimicrobial stewardship initiative at a single academic medical center. The pre-cohort was evaluated through manual electronic medical record (EMR) review, while the post-cohort involved a real-time notification alert system through an electronic clinical surveillance application. The difference in time from positive culture result to antimicrobial therapy optimization before and after implementation of the pharmacist-driven ASI was collected and analyzed. Results: A total of 166 cultures were included in the analysis. Of these, 12/72 (16%) in the pre-cohort and 11/94 (12%) in the post-cohort required antimicrobial therapy modification, with a 21.9-hour reduction in median time from positive culture result to antimicrobial optimization in the post-cohort (43 h vs. 21.1 h; p < 0.01). Similarly, the median time from positive culture result to review was reduced by 20 hours with pharmacist-driven intervention (21.1 h vs. 1.4 h; p < 0.01). Conclusion: The implementation of a pharmacist-driven outpatient antimicrobial stewardship initiative resulted in a significant reduction in time to positive culture review and therapy optimization for patients discharged from the ED of an academic medical center set in Philadelphia, PA. Disclosures: All Authors : No reported disclosures